Perbandingan Reformasi Birokrasi Antara Indonesia dan Malaysia - Nafis, Muhammad Ilham Farhan; Berbudi, Muhammad Aulia; Rambe, Muhammad Naufal Fawwazi; Arteza, Muhammad Fardan; Akhiruzaman, Emiral Ardhi; Risya, Bilqis Hanifa; Yuningsih, Neneng Yani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Bureaucracy has an important role in realizing government functions that are correlated with fulfilling the interests of the people. Basically, the bureaucracy carries out policies that have been formulated by the institutions authorized to form these policies. This is in line with Wright's (ed., 1992) statement in Rohyatin (2021) that the bureaucracy is basically the state machine room. In the process there are challenges and changes that require bureaucratic reform with the aim of achieving good governance in responding to these challenges and changes. Indonesia and Malaysia are two countries that both have bureaucratic reform as their main agenda. This encourages a comparison of bureaucratic reform between Indonesia and Malaysia where the differences and similarities can be seen through bureaucratic reform indicators according to Putra, A. P. & Maulana, A (2022). The results show differences and similarities in bureaucratic reform between Indonesia and Malaysia.